5th Workshop on: Rainfall-runoff Simulation Supporting with GIS and Satellite Data - Akbari, Abolghasem (2016)
Rainfall-runoff simulation is important part of hydrological analysis and design. It is more important when peak runoff and time to peak become a key criteria in design for rural and urban infrastructure. By rapid growing of computer software and earth observation industries, there is high demand to teach/learn of recent advances in integration of GIS tools into the hydrological and hydraulics models supported with remote sensing dataset. It is also provides a better framework for understanding of the hydrological process throughout the visualization and taking the spatial domain into consideration.